2015
DOI: 10.1016/j.jns.2014.12.030
|View full text |Cite
|
Sign up to set email alerts
|

Primary results from the Cervical Dystonia Patient Registry for Observation of OnabotulinumtoxinA Efficacy (CD PROBE)

Abstract: Results indicate robust improvement in clinical ratings and excellent tolerability following onabotulinumtoxinA treatment of CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 24 publications
9
59
0
1
Order By: Relevance
“…As a secondary objective we evaluated for differences in the efficacy of BoNT among these two groups. The demographics of our study population were similar to those reported in the literature when considering age and gender 14,15. Comparison of the underlying diagnoses of our patient population to the literature was difficult as most studies either included only patients with idiopathic cervical dystonia16,19 or included cervical dystonia of any etiology without further delineating underlying diagnoses 12,15,17.…”
Section: Discussionmentioning
confidence: 75%
“…As a secondary objective we evaluated for differences in the efficacy of BoNT among these two groups. The demographics of our study population were similar to those reported in the literature when considering age and gender 14,15. Comparison of the underlying diagnoses of our patient population to the literature was difficult as most studies either included only patients with idiopathic cervical dystonia16,19 or included cervical dystonia of any etiology without further delineating underlying diagnoses 12,15,17.…”
Section: Discussionmentioning
confidence: 75%
“…In a meta-analysis (8 trials with 361 patients using Ona"oNT"; 5 trials with 319 patients using "bo"oNT"), it was shown that there was a statistically and clinically signiicant improvement on objective rating scales and subjective rating scales as well as for pain relief in subjective scales [7]. The same was also seen in a realworld design study (1046 patients) showing robust improvement in clinical ratings as measured via both physician-and subject-reported outcomes and excellent tolerability following Ona"oNT" treatment of CD [30].…”
Section: Treatment Of Cervical Dystoniamentioning
confidence: 66%
“…Reviews of "oNT treatment for CD suggest that 70-90% of patients derive symptomatic beneit from "oNT with at least one injection [29][30][31]. In a meta-analysis (8 trials with 361 patients using Ona"oNT"; 5 trials with 319 patients using "bo"oNT"), it was shown that there was a statistically and clinically signiicant improvement on objective rating scales and subjective rating scales as well as for pain relief in subjective scales [7].…”
Section: Treatment Of Cervical Dystoniamentioning
confidence: 99%
See 2 more Smart Citations